Hubungan Antara Kepercayaan Diri Dengan Penyesuaian Siswa Kelas X SMA N 1 Bae Kudus - Widi Surya Alam; Siti Fitriana; Mujiono Mujiono (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
The background in this study is the importance of self-confidence and self-adjustment for new class students in class X SMA N 1 Bae Kudus. The population in this study were students of class X at SMA N 1 Bae Kudus. This type of research is descriptive quantitative. The sample in the study amounted to 60 students. Retrieval of data using a scale of self-confidence and self-adjustment of students. Data analysis technique using rxy product moment. Based on the results of the research and discussion conducted, it can be concluded that there is a positive and significant relationship between self-confidence and self-adjustment in class X SMA N 1 Bae Kudus. This is shown from the statistical results using the Pearson product moment correlation test to obtain results of (r) = 0.3254 rcount ≥ rtable or 0.3254 ≥ 0.254 when matched with the interpretation table showing that there is a relationship between self-confidence and self-adjustment the strong one. The contribution of the self-confidence variable makes a significant contribution to self-adjustment, namely 302.54% and the rest is determined by other variables. While the significance value of 3.017 is greater than the ttable of 1.67155 indicating a significant relationship between self-confidence and self-adjustment. Thus it shows that there is a relationship between the self-confidence variable and the self-adjustment of class X students of SMA N 1 Bae Kudus. Suggestions for students should have good self-confidence and self-adjustment in order to achieve optimistic and maximum results.